Les sols dégradés révélateurs de la solidarité écologique - Maylis Desrousseaux; Alma Heckenroth (VertigO)
Summary In French law, the principle of ecological solidarity is intended to be implemented when a decision taken by a public authority would have a significant impact on the environment. That is, when the impact has not yet occurred. This interpretation immediately reduces its scope and suggests that it would only apply to areas that have not yet been degraded. Taking the opposite view of the principle, this article demonstrates that the concept of ecological solidarity would also be a driving force in the implementation of measures for the ecological restoration of degraded environments and in particular soils. In doing so, it draws on a field study located in the heart of the Calanques National Park (SynTerCalM project, 2014-2016) to highlight how the inaction toward a degradation that can be invisible, soil contamination, undermines the conservation and restoration objectives of the environments with which it is related.